2020
DOI: 10.5194/bg-17-4707-2020
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing extreme climatic and geochemical conditions during the largest natural mangrove dieback on record

Abstract: Abstract. A massive mangrove dieback event occurred in 2015–2016 along ∼1000 km of pristine coastline in the Gulf of Carpentaria, Australia. Here, we use sediment and wood chronologies to gain insights into geochemical and climatic changes related to this dieback. The unique combination of low rainfall and low sea level observed during the dieback event had been unprecedented in the preceding 3 decades. A combination of iron (Fe) chronologies in wood and sediment, wood density and estimates of mangrove water u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…As the global climate warms 46 , and features of ENSO may change 47 , mangroves are likely to experience further stress (e.g. Sippo et al 17 ). Future investigation could include an examination of changes in the large-scale climate stressors in climate model projections to determine if there is an increased likelihood of experiencing mangrove stress events similar to 2015 in the Gulf of Carpentaria in a warming climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the global climate warms 46 , and features of ENSO may change 47 , mangroves are likely to experience further stress (e.g. Sippo et al 17 ). Future investigation could include an examination of changes in the large-scale climate stressors in climate model projections to determine if there is an increased likelihood of experiencing mangrove stress events similar to 2015 in the Gulf of Carpentaria in a warming climate.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their shallow roots, two mangrove species, particularly Avicennia marina and to a lesser extent Rhizophora stylosa are vulnerable to prolonged below normal sea-levels. Sippo et al 17 concluded that dry conditions combined with porewaters enriched in iron associated with unprecedented below-normal sea levels were the potential causes of the dieback. As a result of months-long episode or permanent sea level drop, a change in the ecosystem can be triggered, with a shift from mangrove forest to drier and more saline saltmarsh, where only a few specialised plants can only grow 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The drought conditions most likely caused accumulative hydric, thermal and radiant stresses (Duke et al, 2017). In addition to low water availability, iron (Fe) toxicity due to a rapid mobilisation of sedimentary Fe and regional variability in groundwater flows may have also played a role in the dieback (Sippo et al, 2020a). The event led to the widespread death of mangrove trees in the region, providing an unfortunate yet unique opportunity to test tree mortality effects on the biogeochemical and ecological functioning of mangroves and capture recovery patterns.…”
Section: Study Sitementioning
confidence: 99%
“…In most cases, recovery of mangroves primarily relies on the recruitment of seedlings (Smith et al, 1994;Krauss and Osland, 2019). Disturbances in mangrove forests not only affect recruitment but can also change the cycling of C, N and S. Loss of mangrove trees and root structures can change organic matter inputs, sediment oxygenation and degradation of sediment organic matter, with consequences for benthic assemblages (Sweetman et al, 2010;Bernardino et al, 2018;Harada et al, 2019), the coastal carbon cycle (Jeffrey et al, 2019;Sippo et al, 2020b), sediment C and N stocks (Adame et al, 2018), microbial assemblages, and associated nutrient processes, e.g. nitrogen fixation and sulfate reduction (Sjöling et al, 2005).…”
mentioning
confidence: 99%
“…These decades of above-average moisture conditions combined with increasing sea level over the same period effectively increased water availability to the mangrove ecosystem 9 , leading to a regional expansion of mangroves across much of northern Australia 7 , 9 , 10 . For Avicennia marina the increased water availability over the preceding decades facilitated a landward intrusion (sampled mangroves that died in 2015–16 in the Gulf of Carpentaria were 30–40 years old) 10 , 11 and hence higher tidal elevation 6 , 9 that left them vulnerable to a subsequent dry period, sudden fall in sea level, or both. Increased water supply to plants almost always results in an increased ratio of leaf to root area 12 , and mangroves with increased leaf to root area ratios are more vulnerable to drought stress 13 .…”
Section: Introductionmentioning
confidence: 99%